Hemorrhagic Meningioma With Symptom of Convulsion: A Rare Presentation of Parietal Meningioma - Dinh Thi Phuong Hoai; Duong Ngoc Thanh Van; Phan Quoc Tho; Nguyen Ngoc Anh Thu; Le Trong Phuoc; Le Trong Hieu; Nguyen Vinh Lac; Vo Ba Tuong; Nguyen Thanh Minh (International Clinical Neuroscience Journal, 2022)
Meningioma is the most common, extra-axial, non-glial intracranial tumor with an incidence of 2.3- 5.5/100000, accounting for 20%-30% of all primary brain tumor diagnoses in adults. Meningiomas associated with intratumoral hemorrhage are very rare occurring in 0.5%-2.4%. of individuals. Herein, we report a rare case of hemorrhagic meningioma with the symptom of convulsion. The case was a 68-year-old woman admitted to the hospital with severe headache and convulsions. Computed tomography revealed an increase in heterogeneous lesion measuring 4×3×2.5 cm at the right parietal lobe. Brain magnetic resonance imaging (MRI) showed a grossly stable homogeneously enhancing extra-axial mass measuring 43×33×28 mm, small calcified peripheral, intratumoral hemorrhage. Histopathology showed a multi-celled meningioma with bleeding areas (WHO grade I).